PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PADA SICEPAT EKSPRESS INDONESIA CABANG PEKANBARU - Syahsudarmi, Siti (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
This research was conducted at SiCepat Express Indonesia Pekanbaru Branch. The purpose of this study was to determine the effect of motivation on the performance of the employees of SiCepat Ekspress Indoneisa Pekanbaru Branch, amounting to 51 people. Sampling was carried out using saturated samples. The variables studied in this study were motivation, and performance. Data analysis using simple linear regression method using validity, reliability, normality, R2, t-test. The test was conducted to determine the relationship between the independent variable (independent variable) and the dependent variable (dependent variable). Based on the results of the study, it was found that motivation had a significant effect on performance with a value of R = 0.677 which indicated a close relationship between motivation and employee performance at SiCepat Ekspress Indoneisa Pekanbaru Branch. Meanwhile, R square is obtained 0.459, which means that motivation has a contribution of 45.9% to the performance of the employees of the Pekanbaru Branch of the Indonesian Express SiCepat. Partially, motivation has a positive and significant effect on the performance of employees of SiCepat Ekspress Indoneisa Pekanbaru Branch with the linear regression equation in this study: Y = 17.564 + 0.521 X + 0.431 X with 0.000 significantly smaller than alpha 0.05. The conclusion in this study is that the partial hypothesis between the motivational variables on employee performance is proven and can be accepted as true.